A smart system to manage the context evolution in the Cultural Heritage domain. (October 2016) - Chianese, Angelo; Piccialli, Francesco
Highlights: Model the context evolution by means of a graph approach. Design a Context Evolution System (CES) to manage the context evolution and the consequently tailoring of data and services. Improve user experience by means of this kind of system. Our apporach is suitable within the Cultural Heritage domain. Abstract: Nowadays intelligent and pervasive environments are characterized by a great number of devices and sensors that develop continuously and capture enormous amounts of data. Designing a context-aware system able to provide the most tailored services to users according to their behaviors, preferences and needs is still a research challenge. In such environments, although the context is very complex, dynamic and full of data captured and produced, users aspire to automatically receive contextualized services. The Cultural Heritage domain represents a domain where exchanged and produced data can be opportunely exploited by a set of applications and services in order to transform a static space into a smart environment. In this perspective, this paper presents a context-aware system named Context Evolution System (CES) able to represent and manage the evolution of the context through its instances; such an evolution is driven by occurring events and opportunely modeled by a graph structure. To assess the proposed solution, a Cultural Heritage case study of a real temporary art exhibition named the Beauty or the Truth and located in Naples (Italy) is presented and discussed.